The Importance of Scientific Evidence for the Work of the German Bundestag - Regina T. Riphahn; Monika Schnitzer (Wirtschaftsdienst)
Abstract The German National Academy of Sciences Leopoldina, under the direction of Regina Riphahn and Monika Schnitzer, commissioned a survey aimed at members of the German Bundestag and their staff. The aim of the survey was to obtain information about the communication needs of the recipients of scientific advice. Scientific findings are highly valued among political representatives. For effective communication, it is helpful to have a clear understanding of political tasks and processes, formats that are appropriate for the target group, as well as visualisations of the findings.